Comprehensive Review of Specialized Nursing Roles in Advancing Healthcare Delivery - Alasmy, Asia Ahmed; Alasmy, Fatimah Ahmed; Alhamdan, Bsmah Abdollah; Mohammed, Rehab Ali; Alshahrani, Fatimah Abdullah Jaber; Alruwaythi, Amal Ayedh; Alrowithi, Sarah Ayedh; Adawi, Ameera Suliman Saeed; Alanazi, Amal Rasheed; Alasiri, Ibtisam Hassan Abdullah (Journal of Ecohumanism, 2024)
Nursing's place in healthcare is changing from a more traditional and static position as healthcare has increasingly focused on specialization in modern times. Advanced nursing roles, including NPs, CNSs, certified registered nurse anesthetists, and clinical nurse educators, have gained growing importance in advancing patient and population health to further increase the accessibility of quality healthcare services as new care challenges arise. This appraisal aims to review the literature on the aspects in which these specialized nursing roles have enhanced the delivery of healthcare. Analyzing the literature and case studies incorporated in the paper reveals these roles' effects on patient outcomes, workforce productivity, and encompassing healthcare organization stability. It also presents the problems associated with employing specialized nurses based on specific regulatory, educational, and financial issues and suggestions about how these professionals can be utilized most effectively in health care.